The Effect of Atmospherer Composition on The Quality of Berastagi Tangerines Fruit (Citrus Nobilis LOUR var Microcarpa) During The Storage at Room Temperature - Marisi Panggabean; Rona J. Nainggolan; Elisa Julianti (Universitas Sumatera Utara, 2016)
This research was conducted to discover the effect of atmosphere composition during storage at room temperature on the quality of Berastagi tangerines. The research was conducted by applying a complete randomly design with two factors, i e atmosphere composition of A1 = concentrations of O2 3-7%, concentrations of CO2 1-3%, A2 = concentrations of O2 8-12%, concentrations of CO2 1-3%, A3 = concentrations of O2 3-7%, concentrations of CO2 4-6%, A4 = concentrations of O2 8-12%, concentrations of CO2 4-6%, and A5 = Control (open air). Length of storage were L1 = 5 days, L2 = 10 days, and L3 = 15 days. The Parameters obsserved were water content, mass loss, vitamin C content, total soluble solids, total acid, hardness, organoleptic of color, smell, taste, and texture. The results of the research showed that atmosphere composition had highly significant effect the water content, mass loss, vitamin C content, total soluble solids, total acid, hardness, organoleptic of color, smell, taste, and texture. The length of storage had highly significant effect on the water content, mass loss, vitamin C content, total soluble solids, total acid, hardness, organoleptic of color, smell, taste, and texture. The longer of the length of the storage , the lower the water content, the vitamin C content, and the total acid, but the higher the mass loss was. The interaction only affected the water content and the total acid. The air composition of O2 3-7%, and CO2 1-3% could maintain the quality of Berastagi tangerine for 15 days. Keyword : Berastagi Tangerines, air composition, storage